Peningkatan pemahaman konsep matematika melalui Realistic Mathematic Education berbantu media konkret pada siswa kelas 1 sekolah dasar - Riski Febrianti; Muhammad Syaipul Hayat; Christin Eni Wati (Jurnal Pendidikan Guru Profesional, 2024)
The aim of this research is to describe the increase in the ability to understand mathematical concepts using Realistic Mathematic Education assisted by concrete object media. The research subjects were class 1B of Kalicari 01 Semarang State Elementary School, totaling 27 children, consisting of 11 male students and 16 female students. The data collection techniques used are observation, tests and documentation. Data analysis in this class research action is quantitative and qualitative data analysis. The research results showed that the ability to understand mathematical concepts in cycle I was 54.07% with low criteria and in cycle II it was 80.87% with high criteria. Based on the research that has been conducted, it can be concluded that the ability to understand mathematical concepts, teachers' teaching skills in managing learning, and student activities in class 1 of Kalicari 01 Semarang State Elementary School increased after the implementation of the Realistic Mathematics Education model assisted by concrete objects as media.